ANALISA PROSES KEBIJAKAN PUBLIK DAN KELEMBAGAAN POLITIK: KASUS RUU PORNOGRAFI DAN PORNOAKSI TAHUN 2006 - ., Nuraina (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2010)
This article explains about how a policy process of public hardly influenced by political importance in institution of politics. In anti pornography draft of law and pornoaksi (RUAPP), there are some factors showing existence of politics importance. This thing seen in political institution that is parliament which in it there is importance of politics either individually and also politics party institute. But which will be studied here is why RUAPP so becomes issue crucial even experiences many conflict of interests in ideology, then why politics institute went forward backing-off to study RUAPP. To study that thing is applied analyzer by using the policy cycle and institution context of politics theory.